Land Degradation Assessment Model Using Field Assessment And RUSLE Methods In Wai Ruhu Watershed, Ambon Island, Mollucas Province - Talakua, Silwanus Matheus; Osok, Rafael Marthinus (Faculty of Geography, Universitas Gadjah Mada, 2025)
Land degradation due to erosion is a serious threat to land sustainability of small tropical islands in Maluku, Indonesia. The current research was carried out in the Wai Ruhu Watershed, Ambon Island, Maluku; it was a part of studies conducted in Maluku in order to develop a suitable land degradation assessment model based on local conditions. Soil loss as the indicator of land degradation were determined using Stocking’s field assessment and RUSLE methods. The study found that land degradation rates in the study area using field indicators ranged from the lowest soil loss 4.40–19.15t/ha/yr to the highest 202.84-675.62t/ha/yr, while the RUSLE method ranged from 0.11-16.92t/ha/yr to the highest 287.63-4207.41t/ha/yr. The developed land degradation model (LD) due to erosion LD = 0.1499xR1.000 xK0.0026xLS0.0933xC0.133xP1.000xBd0.700xAv-0.652 is statistically significant because their p-values equal 0.000 with high R2 of 82,5% at a confidence level of 95%. The second model was also produced with a correction factor of 0.2158, so LD = 0,2158xRxKxLSxCxP, where LD= land degradation (tons/ha/yr), R = rain erosivity value (ton.m/ha/cm-rain), K= soil erodibility index, LS= slope length and steepness factor index, C= plant or vegetation or land use factor index, P= soil conservation practices factor index, Bd= soil bulk weight factor (g/cm3), and Av= vegetation/plant or land use stage factor (years). These results promote the importance fact that the Stocking’s land degradation field assessment indicators could be considered as a suitable land degradation assessment model for the specific local condition of small islands in Maluku.Received: 2024-08-06 Revised: 2025-12-11 Accepted: 2025-12-31 Published: 2025-12-31